Juridical Review of Evidence of Land Eigendom Verponding in The Implementation of Land Acquisition in Indonesia : Judicial Analysis Of The Cassation Decision Number: 211/Pdt.G/2019/PN Amb - Celine Tio; M Tartib; Erniyanti Erniyanti; Soerya Respationo (International Journal of Social Science and Humanity, 2024)
The land system is called eigendom land. However, the land system that uses western law is still considered to be out of sync with human rights and is also detrimental to society, so during Indonesia's independence, new regulations were issued that regulate the national land system. However, in reality, transmitting western law to national law is not easy, so several land disputes have arisen, one of which is the ex eigendom verponding land dispute which was tried at the Ambon City District Court with Supreme Court decision number: 211/Pdt.G/2019/PN Amb . Based on the description in this thesis, the issues that will be discussed are 1) How to regulate land law ex eigendom verponding. 2) How is the implementation related to land ex eigendom verponding. 3) What are the constraint factors and solutions related to ex eigendom verponding land. This research aims to analyze the position of the case, the suitability of the considerations of the Supreme Court judges as well as the strengths and weaknesses of the judges in deciding the verdict in this ex eigendom verponding land dispute case. This research applies normative legal research methods. The results of the discussion produced in this research found that the judge's reasons for rejecting the case application submitted by Lutfi Attamimi as a representative of PT. Maluku Building is in accordance with the facts and applicable law, but there are also several weaknesses in the judge's consideration of the land data evidence attached by the plaintiff, so that at the end of the decision it was concluded that the ex-eigendom Verponding land number 987 was not successfully reclaimed by the plaintiff due to the lack of the validity of the evidence and facts presented before the trial.